4CPS-023 Long term efficacy, safety and adherence to alirocumab in patients with dyslipidaemia from a tertiary hospital cohort. (24th March 2020) - Rodriguez, A; Lopez, C; González-Colominas, E; Luque, S; Recasens, L; Pedro-Botet, J; Oliveras, A; Gonzalez, R; Tarason, L; Grau, S
Abstract : Background and importance: Alirocumab is a monoclonal antibody approved for the treatment of hypercholesterolaemia but long term clinical data are still limited. Aim and objectives: To assess the long term efficacy, safety and adherence to alirocumab after 96 weeks of treatment in a cohort of patients with dyslipidaemia. Material and methods: This was a retrospective observational study performed in a university tertiary hospital. All patients starting alirocumab before September 2017 in our institution and treated for at least 96 weeks were included. Demographic, clinical and alirocumab data were collected. Treatment efficacy was calculated as per cent reduction in low density lipoprotein cholesterol (LDL-c) from baseline to 96 weeks after treatment initiation. Adverse effects were collected and classified according to the common terminology criteria for adverse events (CTCAE) V.4.0 grades. Mean adherence at 96 weeks was calculated by the medication possession ratio based on pharmacy refill records. Results: Thirty-three patients started alirocumab treatment in 2017 and 31 (93.9%) were still on treatment after 96 weeks. Two patients (6.1%) discontinued therapy: one due to an active malignancy and one due to loss of follow-up. Patient characteristics were 58.1% men with a median (IQR) age of 65 (11) years. Alirocumab dose was 75 mg/2 weeks in 87.1% of patients and 150 mg/2 weeks in 12.9%. Secondary prevention was 83.9% and there was a high cardiovascular risk in 80.6%. Type of hypercholesterolaemia was heterozygous familial in 29.0% of patients, polygenic in 67.7% and combined familial hyperlipidaemia in 3.2%. Statin intolerance was found in 38.7% of patients. Comorbidities included diabetes mellitus 19.4%, hypertension 54.8% and smoking 3.2%. Median (range) adherence was 100% (81.7–100%) (only 2 patients (6.5%) with adherence <90%). Median (IQR) reduction in LDL-c reduction was 59.5 (22.6)%. Only one patient did not have a reduction in LDL from baseline (adherence 82%). A high cardiovascular risk was the only patient factor associated with 100% adherence (p=0.034). Mild adverse effects were present in 19.3% of patients (27.3% constipation, 18.2% flu-like syndrome, 18.2% pruritus and other (dizziness, palpitations, headache, dysgeusia) 9.1% each). All adverse effects (100%) were classified as CTCAE grade 1. Conclusion and relevance: More than 90% of patients starting alirocumab persisted with treatment for 96 weeks after initiation. Alirocumab showed good long term efficacy with a median reduction in LDL of >50%. It was also well tolerated because all reported adverse events were mild and did not lead to any treatment discontinuation. References and/or acknowledgements: No conflict of interest.